Novel Blood Clot Retriever for Ischemic Stroke - Ming-Ya Hung; Chun-Kai Yang; Jiong-Hong Chen; Li-Han Lin; Hao-Ming Hsiao (Micromachines, 2021)
Stroke is the second leading cause of death in the world. Ischemic stroke, caused by the blockage of intracranial arteries, accounts for approximately 80% of strokes. Among this proportion, acute ischemic stroke, usually caused by the sudden formation of blood clots, can cause fatal blockages in arteries. We proposed a unique blood clot retriever for the treatment of acute ischemic stroke, and conducted a series of tasks, including design, computer simulation, prototyping, and bench testing, for the proof of concept. Unlike most blood clot retrievers used today, our novel design deviates from traditional stent-like blood clot retrievers and uses large closed cells, irregular spikes, and strut protrusions to achieve maximum entanglement for better retrieval performance. Experimental results showed that the retrieval rate of our blood clot retriever was 79%, which demonstrated the feasibility of our new design concept.